2008
DOI: 10.1093/ije/dyn240
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease and injury in Aboriginal and Torres Strait Islander Peoples: the Indigenous health gap

Abstract: Comprehensive information on the burden of disease for Indigenous Australians is essential for informed health priority setting. This assessment has identified large health gaps which translate into opportunities for large health gains. It provides the empirical base to determine a more equitable and efficient funding of Indigenous health in Australia. The methods are replicable and would benefit priority setting in other countries with great disparities in health experienced by Indigenous peoples or other dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
715
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 599 publications
(737 citation statements)
references
References 6 publications
12
715
2
8
Order By: Relevance
“…Much of the previous work using DALYs to identify health disparities within specific regions has focused on ethnic disparities. [19][20][21][22] However, DALY-gap in slum communities is different from income or indigenous health gap; it addresses disease burden of communities or neighborhoods, making it a metric easier to apply for resource allocation. Furthermore, the spatial analysis in our study showed that the TB burden differs greatly even across different slum and non-slum communities.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the previous work using DALYs to identify health disparities within specific regions has focused on ethnic disparities. [19][20][21][22] However, DALY-gap in slum communities is different from income or indigenous health gap; it addresses disease burden of communities or neighborhoods, making it a metric easier to apply for resource allocation. Furthermore, the spatial analysis in our study showed that the TB burden differs greatly even across different slum and non-slum communities.…”
Section: Discussionmentioning
confidence: 99%
“…As a lasting legacy of the trauma of colonization, systemic discrimination and racism, separation of families, removal from country, and loss of language and culture, Indigenous Australians show poorer outcomes on a range of measures. These include a 10‐plus‐year difference in life expectancy and higher rates of infant mortality, hospitalizations for chronic conditions, injury, and disability 15, 16, 17, 18. The story is similar for mental health.…”
mentioning
confidence: 99%
“…23 The survey asked patients about their risk status for behavioural risk factors and screening history for blood pressure, cholesterol, diabetes and cervical cancer. These items were chosen as they contribute significantly to the burden of disease among Aboriginal and Torres Strait Islander people, 24 and there is evidence that regular screening can improve health outcomes. 2 Included survey items were based on the most recent Australian Bureau of Statistics National Aboriginal and Torres Strait Islander Health Survey collected in 2004-05.…”
Section: Collection Of Self-report Datamentioning
confidence: 99%
“…1 Prevention activities such as regular screening are likely to produce significant health gains. 2 To achieve these gains clinicians need appropriate, valid and reliable measures of a patient's screening history.…”
mentioning
confidence: 99%